Comparative Analysis of Mycoplasma gallisepticum vlhA Promoters - Orlov, Mikhail; Garanina, Irina; Fisunov, Gleb Y.; Sorokin, Anatoly (Frontiers in Genetics, 2018)
Mycoplasma gallisepticum is an intracellular parasite affecting respiratory tract of poultry that belongs to class Mollicutes. M. gallisepticum features numerous variable lipoprotein hemagglutinin genes (vlhA) that play a role in immune escape. The vlhA promoters have a set of distinct properties in comparison to promoters of the other genes. The vlhA promoters carry a variable GAA repeats region at approximately 40 nts upstream of transcription start site. The promoters have been considered active only in the presence of exactly 12 GAA repeats. The mechanisms of vlhA expression regulation and GAA number variation are not described. Here we tried to understand these mechanisms using different computational methods. We conducted a comparative analysis among several M. gallisepticum strains. Nucleotide sequences analysis showed the presence of highly conserved regions flanking repeated trinucleotides that are not linked to GAA number variation. VlhA genes with 12 GAA repeats and their orthologs in 12 M. gallisepticum strains are more conserved than other vlhA genes and have narrower GAA number distribution. We conducted a comparative analysis of physicochemical profiles of M. gallisepticum vlhA and sigma-70 promoters. Stress-Induced Duplex Destabilization (SIDD) profiles showed that sigma-70 group is characterized by the common to prokaryotic promoters sharp maxima while vlhA promoters are hardly destabilized with the region between GAA repeats and transcription start site having zero opening probability. Electrostatic potential profiles of vlhA promoters indicate the presence of the distinct patterns that appear to govern initial stages of specific DNA-protein recognition. Open state dynamics profiles of vlhA demonstrate the pattern that might facilitate transcription bubble formation. Obtained data could be the basis for experimental identification of mechanisms of phase variation in M. gallisepticum.